Analisis Tabungan Paket Lebaran Dalam Perspektif Ekonomi Syari'ah Di Desa Parung Kecamatan Subang Kabupaten Subang: Idah Hamidah - Idah Hamidah Ginanjar; ahmad damiri; Jalaludin Jalaludin (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2019)
This article discusses the analysis of Eid package savings in sharia economy perspective in Parung Village, Subang Subdistrict, Subang Regency. The purpose of this study was to determine the contracting system used in the implementation of Eid savings packages in Parung Village Subang Subdistrict, Subang Regency, Sharia economic review of the implementation of Eid savings packages in Parung Subdistrict Subang Subang Regency, and the impact of the implementation of Eid savings packages in Parung Village Subdistrict Subang Subang Regency, the research method used is qualitative research with an empirical approach. Data collection techniques used were observation, interviews, and documentation. In this study, the data source consisted of Primary Data and Secondary Data. Primary data were obtained from the field results by direct observation and interviews with managers and members of the Eid package in Parung Village, Subang District, Subang Regency. Secondary data was obtained from various references, such as sources from the internet, institutional archives and other readings related to the problem under study. The results showed that the implementation of the Lebaran Package Savings in Parung Village, Subang Sub-District, Subang Regency using the Wadi'ah (savings) agreement as well as the Salam (package) agreement, according to the syari'ah economy this kind of transaction is invalid, because Islam forbids in one transaction there are two contracts at once. However, the presence of Eid savings packages, is very positive contribution to the community, so management should be adjusted to the principles of Islamic sharia. Among them separating savings transactions and Eid packages. Keywords — Savings, Eid Package, Islamic Economy